KEPEMIMPINAN DALAM SISTEM PENJAMINAN MUTU PENDIDIKAN TINGGI - Muhammad, Syuaiban (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
The background of this paper is existence the national policies on quality assurance system of higher education. The purpose is to discuss on role of academic institution leadership, chairman of study program, and lecturers within quality assurance system of higher education. And the methods used is library studies who has the characteristic of objective, systematic, analytic, and descriptive. Now, the conclusion is that leadership of academic institution, chairman of study program, and lecturers, each is play an very important role and absolute necessary within quality assurance system of higher education.